A survey of health practice in Barrio Buray, Oton. - Alincastre, Cecilio; Baylon, Mario; Dumayas, Rodolfo (1979.)
no abstract
Term paper (Undergraduate, Senior Colloquium) Division of Social Sciences, University of the Philippines College, Iloilo. 1979.
Keywords: Health paractice -- Barrio Buray, Oton